Study on Properties of Hydrophobically Associating Polymer in High Salinity Reservoirs - Wang, Kai; Dai, Caili; Zhang, Wangwang; Chen, Hailong; Li, Hui; Wang, Lei; Wu, Xiaoming (Asian Journal of Chemistry, 2014)
Compared with the conventional partially hydrolyzed polyacrylamide, hydrophobically associating polymer performs better in high salinity reservoirs. In this paper, the variation of viscosity is studied under condition of different influencing factors such as concentration, salinity and temperature. The results show that the optimum applicable mass concentration, salinity and temperature is 2500-4000 mg/L, 40500-80500 mg/L and 20-60 °C, respectively. Sandpacking flooding test and anti-shearing test are carried out under laboratory conditions. The results show that the hydrophobically associating polymer after being sheared also has ability to regain its viscosity and the incremental oil recovery obtained in high salinity is higher than conventional polymer flooding, which suggests that it has a wide application prospects in tertiary oil recovery.